Pointing out persuasion in Philemon: Fifty readings of Paul’s rhetoric from the 4th to the 18th century - R. Venter (Acta Theologica)
Read a book announcement on D.F. Tolmie, Pointing out persuasion in Philemon: Fifty readings of Paul’s rhetoric from the 4th to the 18th century. Tübingen: Mohr Siebeck, 383pp.